Analisis Implementasi Kebijakan Study From Home Pelajaran Bahasa Indonesia di Masa Covid-19 - Rully Silvia; Rohmat Tri Sudrajat (Jurnal Guru Indonesia, 2021)
AbstractThis research is to determine the effectiveness of SFH (Study From Home) learning during the pandemic. In addition, to determine the success of learning Indonesian to students during the pandemic. This research was motivated by the Covid-19 pandemic that hit the world which affected all aspects of life, including in the field of education. Schooling cannot be done face-to-face. As a result, student learning is conducted Study From Home (SFH). The method used in this research is descriptive qualitative. Data collection techniques were given through questionnaires and interviews. The data obtained were described descriptively. The research subjects were 48 students of class XII at SMA Negeri 2 Padalarang. The results of the study explain that online learning still has to be improved in terms of various things, such as student difficulties, students difficulties and solutions, effective teaching materials, student learning methods, and assignments. The students' difficulty by understanding the learning material and submit assignments on time. The solution to overcome that issue is by arranging students to search other sources and look for information on social media or to ask friends and teachers. The learning method expected by students is blended learning. For learning media, students chose video. Through videos, students can understand learning easily. If the material or assignments given by the teacher are not understood, students can play the video repeatedly. To be more effective in a way of giving assigments, students can choose between assigments in the from of multiple choice in quizzes or description.Keywords:  Study From Home, Indonesian, Covid-19 AbstrakPenelitian ini bertujuan untuk mengetahui keefektifan pada pembelajaran SFH (Study From Home) di masa pandemi. Selain itu, untuk mengetahui keberhasilan pembelajaran Bahasa Indonesia kepada siswa pada masa pandemi. Penelitian ini dilatarbelakangi adanya pandemi Covid-19 yang melanda dunia yang mempengaruhi seluruh aspek dalam kehidupan, diantaranya dalam bidang pendidikan. Sekolah tidak dapat dilakukan secara tatap muka. Akibatnya pembelajaran siswa dilakukan Studi From Home (SFH). Metode yang dipergunakan dalam penelitian ini adalah kualitatif deskriptif. Teknik pengambilan data diberikan melalui kuesioner dan wawancara.  Data yang diperoleh dijelaskan secara deskriptif. Subjek penelitiannya adalah 48 siswa kelas XII di SMA Negeri 2 Padalarang. Dari hasil penelitian menjelaskan bahwa pembelajaran daring masih harus diperbaiki dari berbagai hal, seperti kesulitan-kesulitan siswa, cara mengatasinya, kendala yang dihadapi, bahan ajar yang efektif, cara belajar siswa, dan pemberian tugasnya. Kesulitan siswa adalah memahami materi pembelajaran dan mengumpulkan tugas tepat waktu. Cara mengatasi kesulitannya, siswa menyelesaikannya dengan membuka sumber lain, mencari informasi di media sosial, bertanya kepada teman, dan bertanya kepada guru. Metode pembelajaran yang diharapkan siswa adalah blended learning. Untuk media pembelajaran, siswa memilih video. Melalui video, siswa dapat memahami pembelajaran dengan mudah. Jika belum dimengerti dari materi dan tugas yang diberikan guru, siswa dapat memutar video secara berulang-ulang. Cara pemberian tugas yang efektif, siswa memilih tugas dalam bentuk kuis dan uraian. Kata kunci:  Study From Home, Bahasa Indonesia, Covid-19